2010
DOI: 10.1111/j.1365-2966.2010.16882.x
|View full text |Cite
|
Sign up to set email alerts
|

PG 1115+080: variations of the A2/A1 flux ratio and new values of the time delays

Abstract: We report the results of our multicolour observations of PG 1115+080 with the 1.5‐m telescope of the Maidanak Observatory (Uzbekistan, Central Asia) in 2001–2006. Monitoring data in filter R spanning the 2004, 2005 and 2006 seasons (76 data points) demonstrate distinct brightness variations of the source quasar with the total amplitude of almost 0.4 mag. Our R light curves have shown image C leading B by 16.4 d and image (A1+A2) by 12 d that is inconsistent with the previous estimates obtained by Schechter et … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
(170 reference statements)
4
9
0
Order By: Relevance
“…The micro-lensing rate measured for the A, B, C components, on average, corresponds to the characteristic rate of micro-lensing 10 −4 mag d −1 reported for other known gravitationally lensed quasars (Gaynullina et al 2005;Vakulik et al 2006;Goicoechea & Shalyapin 2010;Tsvetkova et al 2010;Ricci et al 2011). …”
Section: Micro-lensing Eventssupporting
confidence: 75%
See 1 more Smart Citation
“…The micro-lensing rate measured for the A, B, C components, on average, corresponds to the characteristic rate of micro-lensing 10 −4 mag d −1 reported for other known gravitationally lensed quasars (Gaynullina et al 2005;Vakulik et al 2006;Goicoechea & Shalyapin 2010;Tsvetkova et al 2010;Ricci et al 2011). …”
Section: Micro-lensing Eventssupporting
confidence: 75%
“…The long-term light curves indicate the presence of micro-lensing effects, sometimes displaying a large amplitude with respect to by micro-lensing with induced variability at the level of 10 −4 mag d −1 (Gaynullina et al 2005;Vakulik et al 2006;Goicoechea & Shalyapin 2010;Tsvetkova et al 2010). But here we found out one of the fastest micro-lensing effects with a rate of 10 −3 mag d The flux slope of the B component in 2003 is smaller than those of the other components.…”
Section: I C Ro -L E N S I N G a N D C O L O U R Va R I At I O N Smentioning
confidence: 44%
“…Schechter et al 1997). In this work, we use recent estimates of the time delays by Tsvetkova et al (2010) that differ from previously found values by e.g. Barkana (1997).…”
Section: The Individual Lensesmentioning
confidence: 99%
“…However, as stated above, A1 produces 56% of the total emission detected at Earth at Å 7500 (Tsvetkova et al 2010). We assume, in the absence of any other information, that »56% of the Mg II and C IV line strength is also from A1.…”
Section: Hst Observationsmentioning
confidence: 92%